MARKETING STRATEGIES IN SHARIA TOURISM: EXPLORING CONSUMER BEHAVIOR AND DIGITAL BRANDING FOR SUSTAINABLE GROWTH - Sunaidah, Siti (Berajah Journal, 2024)
Sharia tourism, or Islamic-friendly tourism, has emerged as a growing sector in the global tourism industry, driven by the increasing demand for travel experiences that adhere to Islamic principles. As Muslim travelers seek destinations and services that align with their religious beliefs, the need for effective marketing strategies in this sector has become crucial. This paper explores key marketing strategies employed in Sharia tourism, focusing on the role of digital marketing, branding, and consumer behavior in shaping the growth of this niche market. Through case studies and analysis of successful Sharia-compliant tourism destinations, the research highlights how destinations are leveraging social media, influencer marketing, and content-driven campaigns to attract Muslim travelers. Moreover, this paper discusses the unique challenges faced by marketers in positioning Sharia tourism products while maintaining cultural sensitivity and religious compliance. The research also examines consumer preferences, exploring how elements such as halal food, gender-segregated facilities, and religious accommodations influence the decision-making process of Muslim tourists. The findings suggest that with proper marketing, Sharia tourism can significantly contribute to the growth of the global tourism sector, offering both economic benefits and opportunities for cultural exchange. Lastly, recommendations are provided for tourism marketers to enhance their branding efforts and ensure that their messaging aligns with the values and needs of Muslim travelers.